IMPLEMENTASI HEAD-UP ELEVASI 30° PADA PASIEN STROKE DENGAN RISIKO PERFUSI SEREBRAL TIDAK EFEKTIF - Khasanah, Yunnik Fatun; Fibriansari, Rizeki Dwi; Astuti, Anggia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2024)
Stroke is a condition of lack of oxygen caused by blockage of blood vessels leading to the brain which causes cerebral disorders. A stroke occurs when blood flow to the brain is suddenly blocked for more than 24 hours because a blood vessel is blocked or ruptured. This can occur due to several factors, including uncontrolled blood pressure, headache, dizziness nausea, and vomiting. To overcome some of these problems, non-pharmacological therapy is needed, namely providing a head-up position with an elevation of 30° with the risk that cerebral perfusion can be effective. The aim is to explore medical surgical nursing care using the implementation of head-up elevation in stroke patients with nursing problems at risk of ineffective cerebral perfusion. This research used a case study design conducted on one respondent with the inclusion criteria being age over 50 years and risk factors for hypertension. This research was conducted for 3 days in the Kenanga Room at RSUD dr. Haryoto Lumajang in June 2024. Data collection used interview, observation, and documentation techniques with decisive intervention. The tools or instruments used are head-up SOPs and observation sheets. Implementation of 30° head-up elevation for 30 minutes for three days in stroke patients who were at risk of ineffective cerebral perfusion with initial blood pressure values of 161/101 mmHg to final blood pressure of 141/58 mm Hg and initial MAP results of 121 mmHg and final MAP of 85. 6 mmHg. It is recommended that nurses use it as a working guide for stroke patients with risk problems for ineffective cerebral perfusion through the implementation of 30° elevation head-up intervention. Thus, providing 30° elevation head-up therapy affects reducing intracranial pressure, the aim of which is to maximize venous return so that blood flow to the brain becomes smooth, increasing cerebral tissue metabolism and maximizing oxygenation of brain tissue so that the brain becomes more active.